2011
DOI: 10.12968/bjon.2011.20.22.1426
|View full text |Cite
|
Sign up to set email alerts
|

Anti-embolism stockings and proximal indentation

Abstract: The authors of this study noticed that the elastic garters of below knee anti-embolism stockings (AES) were indenting the proximal calves of patients after application and feared this might be interrupting venous return. This was lower on one ward which had a rigorous standardized protocol for sizing and checking stockings. Hypotheses were that proximal indentation caused higher proximal than distal pressures (reverse gradients) and that by adopting the standardized protocol throughout the unit, proximal inden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 14 publications
0
15
0
Order By: Relevance
“…Incorrect use related to wearing incorrectly sized stockings or to the stocking rolling down, binding or wrinkling. In a study involving an audit and a trial of knee-length GCSs, 85 74% of patients were wearing stockings that were incorrectly sized. Implementation of a standardised protocol within the study setting resulted in statistically significant reduction in this proportion to 34%.…”
Section: Results Of Clinical Evidence Reviewsmentioning
confidence: 99%
See 4 more Smart Citations
“…Incorrect use related to wearing incorrectly sized stockings or to the stocking rolling down, binding or wrinkling. In a study involving an audit and a trial of knee-length GCSs, 85 74% of patients were wearing stockings that were incorrectly sized. Implementation of a standardised protocol within the study setting resulted in statistically significant reduction in this proportion to 34%.…”
Section: Results Of Clinical Evidence Reviewsmentioning
confidence: 99%
“…21,24,25,32,37,60,63,65 One additional RCT 14 and seven observational studies (eight articles) were identified. 15,16,[80][81][82][83][84][85] These additional studies did not meet criteria for inclusion in the review of RCTs of clinical effectiveness, but did provide some data on patient adherence and/or preference.…”
Section: Patient Adherence and Preferencementioning
confidence: 99%
See 3 more Smart Citations